Inositol‐1, 4, 5‐trisphosphate induced Ca2+ release and excitation–contraction coupling in atrial myocytes from normal and failing hearts. (22nd December 2014) - Hohendanner, Felix; Walther, Stefanie; Maxwell, Joshua T.; Kettlewell, Sarah; Awad, Sawsan; Smith, Godfrey L.; Lonchyna, Vassyl A.; Blatter, Lothar A.
<x xml:space="preserve">Abstract</x> Key points Impaired calcium (Ca2+) signalling is the main contributor to depressed ventricular contractile function and occurrence of arrhythmia in heart failure (HF). Here we report that in atrial cells of a rabbit HF model, Ca2+ signalling is enhanced and we identified the underlying cellular mechanisms. Enhanced Ca2+ transients (CaTs) are due to upregulation of inositol‐1, 4, 5‐trisphosphate receptor induced Ca2+ release (IICR) and decreased mitochondrial Ca2+ sequestration. Enhanced IICR, however, together with an increased activity of the sodium–calcium exchange mechanism, also facilitates spontaneous Ca2+ release in form of arrhythmogenic Ca2+ waves and spontaneous action potentials, thus enhancing the arrhythmogenic potential of atrial cells. Our data show that enhanced Ca2+ signalling in HF provides atrial cells with a mechanism to improve ventricular filling and to maintain cardiac output, but also increases the susceptibility to develop atrial arrhythmias facilitated by spontaneous Ca2+ release. Abstract We studied excitation–contraction coupling (ECC) and inositol‐1, 4, 5‐triphosphate (IP3)‐dependent Ca2+ release in normal and heart failure (HF) rabbit atrial cells. Left ventricular HF was induced by combined volume and pressure overload. In HF atrial myocytes diastolic [Ca2+]i was increased, action potential (AP)‐induced Ca2+ transients (CaTs) were larger in amplitude, primarily due to enhanced Ca2+ release from central non‐junctional sarcoplasmic reticulum (SR) and centripetal propagation of activation was accelerated, whereas HF ventricular CaTs were depressed. The larger CaTs were due to enhanced IP3 receptor‐induced Ca2+ release (IICR) and reduced mitochondrial Ca2+ buffering, consistent with a reduced mitochondrial density and Ca2+ uptake capacity in HF. Elementary IP3 receptor‐mediated Ca2+ release events (Ca2+ puffs) were more frequent in HF atrial myoctes and were detected more often in central regions of the non‐junctional SR compared to normal cells. HF cells had an overall higher frequency of spontaneous Ca2+ waves and a larger fraction of waves (termed arrhythmogenic Ca2+ waves) triggered APs and global CaTs. The higher propensity of arrhythmogenic Ca2+ waves resulted from the combined action of enhanced IICR and increased activity of sarcolemmal Na+–Ca2+ exchange depolarizing the cell membrane. In conclusion, the data support the hypothesis that in atrial myocytes from hearts with left ventricular failure, enhanced CaTs during ECC exert positive inotropic effects on atrial contractility which facilitates ventricular filling and contributes to maintaining cardiac output. However, HF atrial cells were also more susceptible to developing arrhythmogenic Ca2+ waves which might form the substrate for atrial rhythm disorders frequently encountered in HF.